2008
DOI: 10.35536/lje.2008.v13.i2.a4
|View full text |Cite
|
Sign up to set email alerts
|

Export-Led Growth Hypothesis in Pakistan: A Reinvestigation Using the Bounds Test

Abstract: Trade is presumed to act as a catalyst to economic growth. This paper reinvestigates the export-led growth hypothesis in Pakistan by using annual time series data on exports, imports, terms of trade, and the labor force participation rate as explanatory variables and gross domestic product (GDP) as the dependent variable for the period 1971-2005. The study uses the more comprehensive and recent bounds test or autoregressive distributed lag model (ARDL) proposed by Pesaran et al (2001) to examine the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In this way, they adopt the new techniques and try to diminish different inefficiencies which exist in the local markets. Numerous studies, confirm the relationship between the exports and economic growth (Siddiqui, et al (2008), Alam (2011) and Shirazi and Manap (2005) etc).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this way, they adopt the new techniques and try to diminish different inefficiencies which exist in the local markets. Numerous studies, confirm the relationship between the exports and economic growth (Siddiqui, et al (2008), Alam (2011) and Shirazi and Manap (2005) etc).…”
Section: Introductionmentioning
confidence: 86%
“…They have found that majority of the countries have short run effect of export in econmic growth in both direction while in long run, 60% export led hypothesis is supported and 40% output led hypothsis is supported in the above mentioned study. Siddiqui et al (2008) re-investigated the causality between export and economic growth in case of Pakistan. They have used more than two variables exports, imports, terms of trade, and the labor force participation rate as explanatory variables and GDP as the dependent variable for 1971-2005 and used the more broad and recent bounds test or ARDL.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The second step relates to the long-term relationship variables and determining their value, and assessment of the short-term elasticity of variables showing the error correction representation of the ARDL model. The result of the error correction model tells us about the speed of adjustment from the short-term shock to the long-term balance (Siddiqui et al, 2008;Kurtovic et al, 2016). The ARDL model is represented by the following equations:…”
Section: Methodsmentioning
confidence: 99%
“…Finally, diagnostic and stability tests are used to assess the reliability of ARDL models. The assessment of the diagnostic tests includes Lagrange Multiplier test, the Ramsey Reset test, the Jarque-Berra test and the KB test (Siddiqui et al, 2008;Kurtovic et al, 2016). Stability tests of variables are carried out by applying cumulative sum of squared recursive residuals, cumulative addition of recursive residuals (CUSUM), and cumulative sum of squared recursive residuals (CUSUMSQ) (Kurtovic et al, 2016).…”
Section: Methodsmentioning
confidence: 99%